Wawasan Al-Qur’an Tentang Ekologi: Kajian Tematik Ayat-ayat Konservasi Lingkungan
As hudan li al-na>s, The Qur’an is certainly not only a metaphysical-eschatological sense, but also concerns to the practical problems of human life in the world, includes the basic guidelines on how humans take care of the universe and conserve the environment. This paper introduced some ways or humans efforts in conserving the environment. This study focused on the searching of verses on ecology, and it also examined verses relating to environmental conservation in the Qur’an by using thematic method. It was found that the verses about the ecology introduced by the Qur'an were in the form of an environment (al-bi>ah), the whole world (al-‘a>lami>n), the sky or universe (al-sama>’), earth (al-ard